FAKTOR-FAKTOR YANG MENDORONG MASYARAKAT DESA LABUHAN RATU VII IKUT SERTA DALAM KEMITRAAN KONSERVASI DI TAMAN NASIONAL WAY KAMBAS - Intan Maharani Safitri; Susni Herwanti; Indra Gumay Febryano; Rudi Hilmanto; Kuswandono Kuswandono; Rusdianto Rusdianto (Forestry Study Program University Of Mataram, 2023)
One of the alternative solution to resolve conflict between communities and conservation area managers is conservation partnership scheme. This study aims to explain the factors that encourage communities to participate in conservation partnership programs in villages around the national park. This study uses a qualitative approach, where data collection is carried out by in-depth interviews, observations, and documentation studies. The collected data is then analyzed to see the factors that encourage communities to participate in conservation partnerships. This study indicates that there are several factors that encourage the community to participate in the program. The first factor is public awareness on the importance of forests, which sparks the will to conserve and protect them. Other factors that the community can obtain are: increased income, permanent jobs, access to assistance and funding from third parties. The community is greatly assisted in terms of the economy after participating in the conservation partnership program activities. Illegal activities, and land fires have been significantly reduced in the Way Kambas National Park area. This shows that the Conservation Partnership in Labuhan Ratu VII Village is starting to succeed, therefore this program can be implemented in other villages. Way Kambas National Park managers should carry out ongoing mentoring and consultation activities in every village around the national park, so that more people will join the conservation partnership program.